2020
DOI: 10.1001/jamanetworkopen.2020.5123
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Bariatric Interventions With Micronutrient and Endocrine Disturbances

Abstract: IMPORTANCE Few studies have described the longitudinal trajectories of serum levels of micronutrients whose deficiencies are associated with serious sequelae following bariatric procedures, such as anemia, osteoporotic fractures, and neuropathies. Furthermore, previous studies comparing laparoscopic sleeve gastrectomy (LSG) vs Roux-en-Y gastric bypass (LRYGB) or one-anastomosis gastric bypass (OAGB) procedures may have been limited by selection and confounding biases.OBJECTIVE To appraise the spectrum and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…al. [ 32 ]. In this study, both groups, over the 2-year period showed a significant reduction in mean values of protein, ferritin and vitamin D, however an improvement in mean values of CRP, insulin and FBGL.…”
Section: Discussionmentioning
confidence: 99%
“…al. [ 32 ]. In this study, both groups, over the 2-year period showed a significant reduction in mean values of protein, ferritin and vitamin D, however an improvement in mean values of CRP, insulin and FBGL.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial search identified a total of 5234 potentially relevant citations. Following screening, a total of 49 studies with 12,880 patients were eligible for inclusion 4,6,21–67 . Of these, five were randomized controlled trials, 33 were retrospective cohort studies, 10 were prospective cohort studies, and one was a nested case–control study.…”
Section: Resultsmentioning
confidence: 99%
“…Forty percent (6/15) 23,29,37,41,62,67 and 52% (12/23) 3 of studies reported successful prevention of ID using their treatment regimen containing <45 mg and ≥45 mg of elemental iron, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a higher incidence of complications after RYGB have been reported, such as fall-related accidents, kidney stones and diseases, gastrointestinal disorders, micronutrient deficiencies, endocrine derangements [ 26 , 51 , 52 ] with respect to SG, which is considered to be a less technically demanding procedure. Furthermore, an increase in costs and hospitalization rates [ 26 , 29 , 30 , 38 , 39 , 41 , 53 ] were described after RYGB, with increased percentages of readmission, re-operation, and subsequent invasive procedures (frequently, complications due to the procedures, such as ventral hernia repair, small bowel obstruction, and gastric revision).…”
Section: Discussionmentioning
confidence: 99%